Plasmodium falciparum non-synonymous Kelch13 mutations mediating artemisinin resistance in East Africa: A systematic review and meta-analysis: 2014–2024 - Anthony Kapesa; Vito Baraka; Richard Mwaiswelo; Maria Zinga; Karol J. Marwa; Eliningaya J. Kweka; Erasmus Kamugisha (PLoS ONE, 2026)
Background Resistance to antimalarial drugs has posed a significant challenge to global efforts to control and eliminate malaria. Partial artemisinin resistance has been observed in East Africa, a region that has been a historical hotspot for antimalarial drug resistance across the continent. Consequently, this review assesses the extent of non-synonymous mutations mediating artemisinin resistance, the varieties of these mutations, and their effects on treatment outcomes in East Africa. Methods Studies reporting artemisinin resistance (samples collected between 2014 and 2024), particularly the Pf-Kelch13 mutation among malaria patients in East Africa, were searched through the Medline, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS, and EMBASE online databases. The protocol for the review was registered at PROSPERO (Reference number: CRD42024602752). Two independent reviewers extracted data. Potential publication bias was assessed using a funnel plot. Pooled proportion estimates were calculated using a random-effects model, and heterogeneity was assessed using I 2 statistics. Results Twenty-four (24) studies were deemed eligible for data extraction. The heterogeneity among the studies included in the meta-analysis was high (I 2 > 95% and p < 0.01). The overall estimated pooled proportions of non-synonymous Pf-Kelch13 mutations, using the random effects model, were 5.0% (95% CI 3.0%–7.0%), with the pooled proportion estimates being higher in Rwanda and Uganda (10.0%, 95% CI 4.0%–16.0%) and (10.0%, 95% CI 6.0%–14.0%), respectively. Subgroup analysis (per mutation type) revealed that R561H and A675V were the most prevalent non-synonymous mutations (9.0%, 95% CI 5.0%–15.0% and 7.0%, 95% CI 4.0%–10.0%, respectively). Patients harbouring parasites with Pf-Kelch13 non-synonymous mutations were significantly more likely to experience treatment failure than those harbouring wild P. falciparum parasites (Log OR: −2.06, 95% CI, −2.71–1.41). Conclusion The prevalence of Pf-Kelch13 non-synonymous mutations known to be associated with artemisinin resistance was significant. The most common mutations identified were R561H and A675V. Continued molecular surveillance and coordinated efforts are essential to contain the partial artemisinin resistance in the East African region and prevent its spread across the continent.